Lobsters with pre-existing damage to their mechanosensory statocyst organs do not incur further damage from exposure to seismic air gun signals. (December 2020) - Day, Ryan D.; Fitzgibbon, Quinn P.; McCauley, Robert D.; Hartmann, Klaas; Semmens, Jayson M.
Abstract: Staotcysts, the mechanosensory organs common to many marine invertebrates, have shown sensitivity to aquatic noise. Previously, rock lobsters ( Jasus edwardsii ) from a remote site with little exposure to anthropogenic noise incurred persistent damage to the statocyst and righting reflex following exposure to seismic air gun signals. Here, J. edwardsii collected from a site subject to high levels of anthropogenic noise were exposed to an equivalent seismic air gun signal regime as the previous study of noise-naïve lobsters. Following exposure, both control and exposed treatments were found to have damage to the statocyst equivalent to that of noise-naïve lobsters following seismic exposure, which led to the conclusion that the damage was pre-existing and not exacerbated by seismic exposure. The source of the damage in the lobsters in this study could not be ascertained, but the soundscape comparisons of the collection sites showed that the noisy site had a 5–10 dB greater level of noise, equivalent to a 3–10 times greater intensity, in the 10–700 Hz range than was found at the remote collection site. In addition to the lack of further damage following seismic exposure, no disruption to the righting reflex was observed. Indeed, compared to the noise naïve lobsters, the lobsters here demonstrated an ability to cope with or adapt to the mechanosensory damage, indicating a need for better understanding of the ecological impacts of the damage caused by low frequency noise on marine organisms. More broadly, this study raises historical exposure to noise as a previously unrecognised but vitally important consideration for studies of aquatic noise. Graphical abstract: Image 1 Highlights: Seismic air gun exposure has been shown to harm invertebrate sensory organs. Lobsters collected from a noisy site showed pre-existing damage to the statocyst. Exposure to seismic air guns did not cause any further damage. Environmental noise exposure was sufficient to reach maximum damage threshold.